Validity of the Open Barbell and Tendo Weightlifting Analyzer Systems versus the Optotrak Certus 3D Motion-Capture System for barbell velocity - Goldsmith, J. A.; Trepeck, C.; Halle, J. L.; Mendez, K. M.; Klemp, A.; Cooke, D. M.; Haischer, M. H.; Byrnes, R. K.; Zoeller, R. F.; Whitehurst, M.; Zourdos, M. C. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To examine the validity of 2 linear position transducers, the Tendo Weightlifting Analyzer System (TWAS) and Open Barbell System (OBS), compared with a criterion device, the Optotrak Certus 3-dimensional motion-capture system (OC3D). Methods: A total of 25 men (age, 25 [3] y; height, 174.0 [6.7] cm; body mass, 89.0 [14.7] kg; squat 1-repetition maximum [1RM], 175.8 [34.7] kg) with >/= 2 y of resistance-training experience completed a back 1RM and 1 set to failure at 70% of 1RM. Average concentric velocity (ACV) and peak concentric velocity (PCV) were recorded by all 3 devices during the final warm-up set, all 1RM attempts, and every repetition during the 70% set. Results: In total, 575 samples were obtained. Bland-Altman plots, mountain plots, a 1-way analysis of variance, SEM, and intraclass correlation coefficients were used to analyze validity. The analysis of variance showed no difference (P = .089) between devices for ACV. However, for PCV, TWAS was significantly different (ie, inaccurate) from OC3D (P < .001) and OBS (P = .001), but OBS was similar (P = .412) to OC3D. For ACV, intraclass correlation coefficients were higher for OBS than for TWAS. Bland-Altman plots showed agreement for ACV for both devices against OC3D but large limits of agreement for PCV for both devices. Mountain plots showed valid ACV for both devices, however, but slightly greater ACV and PCV accuracy with OBS than TWAS. Conclusions: Both devices may provide valid ACV measurements, but some metrics suggest more accurate ACV with OBS vs TWAS. For PCV, neither device is particularly accurate; however, OBS seems to be more accurate than TWAS.